Information Technology Social Impact: The Role of Medical and Biological Texts Content in The Formation of The Students' Literacy - N.A. Antonova; S.V. Kraineva; O. R. Shefer; T.N. Lebedeva; E. N. Erentraut; Y. A. Akhkamova (Communications of International Proceedings, 2022)
The minute-by-minute use of new information technologies has a detrimental effect on the development of the personality of the future specialist. Every year the level of reading literacy is falling sharply. The article proposes the formation of reading literacy among students of the Faculty of primary Classes of the South Ural State Humanitarian Pedagogical University through the use of texts of medical and biological content. The experiment made it possible to prove the hypothesis put forward: the formation of reader's literacy will be successful if texts on reading and comprehension of medical and biological orientation are offered in the study of natural science disciplines.
Keywords: reader's literacy; the study of natural sciences; texts of medical and biological content; students